Determination of inorganic anions in papermaking waters by ion chromatography - Žarković Darja; Todorović Žaklina; Krgović Milorad; Rajaković Ljubinka (Journal of the Serbian Chemical Society, 2009)
A suppressed ion chromatography (IC) method for the determination of inorganic anions in process water from paperboard production was developed and validated. Common inorganic anions (Cl-, NO-3, PO 3-4 and SO2-4) were detected in fresh and process water samples collected from a paperboard production system at 16 characteristic points. It was shown that the use of an IonPac®-AS14 column under isocratic conditions with Na2CO3/NaHCO3 as the eluent and a suppression device proved to be a reliable analytical solution for the separation of the inorganic anions present in papermaking waters. This IC method is quite satisfactory concerning selectivity and sensitivity, and enables the determination of several inorganic anions over a wide concentration range. According to the obtained results, the total amount of analyzed inorganic anions was below 0.1 g/L, i.e., below the critical value which may trigger operational problems in paper production.